Fear of Crime in an Island Paradise: Examining the Generalizability of Key Theoretical Constructs in the Maldivian Context - Hodgkinson, Tarah (International criminal justice review, 2017)
Numerous empirical studies have examined fear of crime. Key theoretical constructs include age, gender, vulnerability, marital status, social cohesion, social incivilities, and perceptions of police. While these constructs have extensive empirical support from cross-sectional and longitudinal projects, they focused on Western liberal democratic nations. Little research exists on fear of crime and its correlates within smaller, island nation-states. The current study (N = 480) examines (a) the prevalence of fear of crime within the Maldives and (b) the extent to which previous theoretical constructs can be generalized to other population areas. Findings demonstrate levels of fear of crime in the Maldives consistent with Western liberal democratic societies but that only certain previous theoretical constructs are associated with variations in fear of crime.